In situ correction of various β-thalassemia mutations in human hematopoietic stem cells - Yang, Yinghong; He, Lina; Xie, Yingjun; Zhu, Lifen; Wu, Jianfeng; Fan, Yong; Yang, Yi; Sun, Xiaofang (Frontiers in Cell and Developmental Biology, 2024)
β-Thalassemia (β-thal) is the most common monogenic disorder caused by various mutations in the human hemoglobin β (HBB) gene and affecting millions of people worldwide. Electroporation of Cas9 and single guide RNA (sgRNA) RNP complexes mediated gene targeting in patient-derived hematopoietic stem cells (HSCs), followed by autologous transplantation, holds the promise to cure patients lacking a compatible bone marrow donor. In this study, a universal gene correction method was devised to achieve in-situ correction of most types of HBB mutations by using validated CRISPR/sgRNA RNP complexes and rAAV6-donor mediated homology directed repair (HDR) in HSCs. The gene edited HSCs exhibited multilineage formation abilities and the expression of β-globin transcripts was restored in differentiated erythroid cells. The method was applied to efficiently correct different mutations in β-thal patient-derived HSCs and the edited HSCs retained the ability to engraft into bone marrow of immunodeficient NOD-scid-IL2Rg−/− (NSI) mice. This study provides an efficient and safe approach for targeting HSCs by HDR at the HBB locus, which provides a potential therapeutic approach for treating other types of monogenic diseases in patient-specific HSCs.